CEO Characteristics and Enterprise Risk Management: The Moderating Role of ESG Disclosure in Indonesian Agro-Industrial Firms - Markus Apriono; Bayu Aprillianto; Isti Fadah; Nining Ika Wahyuni; Nurul Syazwani Mohd Noor (Universitas Trunojoyo Madura, 2026)
This study examines the effect of CEO characteristics on Enterprise Risk Management (ERM) implementation and investigates the moderating role of Environmental, Social, and Governance (ESG) disclosure in Indonesian agro-industrial firms. This study argues that executive demographic and professional attributes shape enterprise risk management practices, while ESG disclosure functions as a governance mechanism that may condition this relationship. Using a quantitative approach, the sample consists of 51 firm-year observations of agro-industrial companies listed on the Indonesia Stock Exchange during 2020–2022. CEO characteristics are constructed using Principal Component Analysis (PCA) based on age, education background, prior executive experience, and tenure. ERM is measured using a composite index, while ESG disclosure is assessed through a disclosure index. The results show that CEO characteristics positively and significantly influence ERM implementation, indicating that executive attributes play a crucial role in shaping integrated risk management structures. Furthermore, ESG disclosure significantly moderates the relationship between CEO characteristics and ERM with a negative interaction effect, suggesting a governance substitution effect. These findings contribute to the literature by integrating an emerging market agro-industrial context. The study highlights the strategic importance of leadership quality and ESG institutionalization in strengthening corporate resilience against environmental and business uncertainties